(3QSGdI aj ZjHI GdEeGe Ydis - (3eMeO Hf eMeO Hf GdfYeGf Hf YHO GdSdGe GdYcHQqj, CHh YHO Gddg, GdeajO, hjYQa HGHf GdeYde , J (B413 (3g`s ((3GdcGXejI s)
(3ChdgG (B:s
(3bGd GdTjN QVi Gddg Yfg MVQJ eLdS QFjS ef GdQDSGA aMQi cdGe ai GdEeGeI aGfJgi Edi Gdbhd ai GdZjHI s
(3BNQgG (B:s
(3hgPG hGVM ade jCJ HTF hddg GdMeO hdQShdg hBdg hGdUdGg hGdSdGe s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI(B_ (3GdfLa (B(998) s
Keywords: (3GdJhMjO hGdedd hGdfMds